ANTHABOGA SITE AS A SYMBOL OF TOLERANCE BETWEEN SUMBERGONDO VILLAGES - Sri Wahyuni; Muhammad Elby (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2019)
The Anthaboga site is a temple and petirtan as a cultural site and is one of the Rsi Markandheya sites which stretches between the Great Temple of Gumuk Kancil, Anthaboga to Gumuk Payung. Although the Anthaboga Site has been known as a place of worship for Hindus, it must be recognized that the Anthaboga Site is the only religious tourism site for 6 religious people at once, namely: Islam, Buddhism, Hinduism, Christianity and Catholicism. This research on the Anthaboga site outlines the history and function of the Anthaboga Site, the values ​​contained and the meaning of tolerance behind the Anthaboga Site while also revealing the role of the local government in the Anthaboga Site. In general, this study aims to obtain an overview and understanding of the history of the Anthaboga Site, Sumbergondo Village. Likewise, to find out the historical values ​​that exist in the Anthaboga Site and to add insight and repertoire of knowledge to the public, especially to the author. This research is a qualitative research. Data collection is done by means of observation, interviews, and documentation, then will be processed using descriptive analysis methods. the results show that there is a very good tolerance but attention from the government is still lacking especially for the preservation of the site